Eye Tracking-based Analysis of Customer Interest on The Effectiveness of Eco-friendly Product Advertising Content - Ghalda Khairunnisa; Hasrini Sari (Jurnal Optimasi Sistem Industri, 2023)
Amid the escalating environmental crisis that has prompted consumers to adopt eco-friendly lifestyles, the popularity of eco-friendly personal care products is increasing significantly. Nevertheless, marketing these products presents challenges that include inadequate product information, perceived unaffordable prices, and relatively low consumer trust. These challenges present an opportunity for the marketing field to increase consumer interest, particularly through advertising, an important medium for disseminating product information. Recognizing the importance of advertising components in influencing consumer preferences, this study uses eye-tracking to identify critical elements in promoting eco-friendly personal care products. The components examined include information on environmental and personal benefits, the presence or absence of price information, and the presentation of an environmental label (logo and text) in advertising. Each of the 43 participants is confronted with eight carefully crafted advertising stimuli. The results of the study highlight the significant influence of clear benefits and price information on consumer preferences, while indicating that eco-label display does not have a significant impact on consumer preference. This research is intended to serve as a source of actionable marketing strategies and is intended to help promote eco-friendly products and increase consumer interest through targeted and effective advertising.